Can atrophic‐erosive oral lichen planus promote cardiovascular diseases? A population‐based study. (26th February 2018) - Conrotto, D; Barattero, R; Carbone, M; Gambino, A; Sciannameo, V; Ricceri, F; Conrotto, F; Broccoletti, R; Arduino, P‐G
Abstract : Objective: Lichen planus has been recently associated with an increased risk of cardiovascular diseases (CVDs). The oral manifestations can be divided into white hyperkeratotic lesions (WL) and atrophic and erosive lesions (RL). The aim of this report was to compare the presence of CVDs between patients affected by WL or RL, to test the hypothesis that RL are associated with an increased incidence of CVDs. Subjects and methods: Patients were analysed through a complete collection of all the risk factors for CVDs. The primary endpoint was the occurrence of a cardiovascular event—acute coronary syndrome (ACS), any revascularization or stroke/TIA. A multivariable logistic regression model, adjusted for age at diagnosis, body mass index, smoking, alcohol consumption, diabetes, hypertension, CVDs familiarity and periodontitis, was performed. Results: A prospective cohort of 307 patients has been evaluated; 185 (60.3%) had WL and 122 RL (39.7%). Twenty‐four patients had a CVD. ACS occurred more frequently in RL (adjusted odds ratio 5.83; 95% CI: 1.16—29.39), mainly due to the higher risk of it after the histological diagnosis of Oral lichen planus OLP (odds ratio 4.23; 95% CI: 0.66—27.23). Conclusion: Patients with RL could possibly have a higher risk of developing ACS. Further analysis on larger cohort is however warranted.